Clinical usefulness of non‐protein respiratory quotient measurement in non‐alcoholic fatty liver disease. Issue 12 (19th March 2013) - Korenaga, Keiko; Korenaga, Masaaki; Teramoto, Fusako; Suzuki, Toshiko; Nishina, Sohji; Sasaki, Kyo; Nakashima, Yoshihiro; Tomiyama, Yasuyuki; Yoshioka, Naoko; Hara, Yuichi; Moriya, Takuya; Hino, Keisuke
<x xml:space="preserve">Abstract</x> Aim Little is known about the effects of non‐alcoholic fatty liver disease (NAFLD) on energy metabolism, although this disease is associated with metabolic syndrome. We measured non‐protein respiratory quotient (npRQ) using indirect calorimetry, which reflects glucose oxidation, and compared this value with histological disease severity in NAFLD patients. Methods Subjects were 32 patients who were diagnosed with NAFLD histopathologically. Subjects underwent body composition analysis and indirect calorimetry, and npRQ was calculated. An oral glucose tolerance test was performed, and plasma glucose area under the curve (AUC glucose) was calculated. Results There were no differences in body mass index, body fat percentage or visceral fat area among fibrosis stage groups. As fibrosis progressed, npRQ significantly decreased (stage 0, 0.895 ± 0.068; stage 1, 0.869 ± 0.067; stage 2, 0.808 ± 0.046; stage 3, 0.798 ± 0.026; P < 0.005). Glucose intolerance worsened and insulin resistance increased with fibrosis stage. npRQ was negatively correlated with AUC glucose (R = −0.6308, P < 0.001), Homeostasis Model of Assessment – Insulin Resistance (R = −0.5045, P < 0.005), fasting glucose (R = −0.4585, P < 0.01) and insulin levels (R = −0.4431, P < 0.05), suggesting that decreased npRQ may reflect impaired glucose tolerance due to insulin resistance, which was associated with fibrosis progression. Estimation of fibrosis stage using npRQ was as accurate as several previously established scoring systems using receiver–operator curve analysis. Conclusion npRQ was significantly decreased in patients with advanced NAFLD. Our data suggest that measurement of npRQ is useful for the estimation of disease severity in NAFLD patients.